Mathematical modelling of industrial enterprise logistics with different options of basic information - Несторенко, Александр Васильевич (Technology audit and production reserves, 2014)
The reasons of the low effectiveness of warehousing models with deficit and their construction are investigated and analyzed. It is not taken into account that the cost of delivery and storage, as well as penalties of shortages related to different moments in time in determining the function form of the general costs in models with a deficit The deficit size and the financial losses from its inception is incorrectly defined. The combination of these observations is one of the main factors affecting the adequacy of mathematical models of inventory management with a deficit. Mathematical models based on the principle of incoming and outgoing financial flows reduction to one moment of time led to the following conclusions: non-compensable deficit allowing is economically inefficient; for "large" penalties from a deficit the compensated deficit allow economically inefficient; the compensated deficit is planned for"small" penalties from a deficit. The planning results differ significantly from the results obtained using the existing model. Using the developed mathematical models will help make the best decisions in warehouse logistics. Remarks on the model construction with a deficit can be used for other models of inventory management that will create an effective information logistics system.